Pharmacognostic evaluation of Terminalia chebula standard extracts and finished products - Gunasekar, Conjeevaram J. (2019)
The different commercial samples of Terminalia chebula (T. chebula) standard extracts and finished products were taken for elemental analysis studies and were evaluated by ICP-OES and compared with standard reference data. Trace elements are naturally occurring and its daily requirement as dietary supplement form is only a few milligrams and even micrograms. They are categorized as essential and non-essential, and that is based upon their biological action, diseases that occur due to their deficiency and toxicity due to overdose. Use of herbal medicines is now increasing worldwide because of their minimal side effects. In general, Haritaki (T. chebula) acts as a blood purifier and prevents haemorrhage. It is also used as an internal cleanser by removing harmful toxins and excess fats out of the body. It can strengthen the hair roots and enriches hair color. The elements were determined quantitatively using the modern technique of ICP-OES. The extracts undertaken for this study contains Ca as a primary elemental content, and its concentration is found to be as high as 144 mg/kg in comparison with other macro elements. Ca helps to overcome the problems of high blood pressure, heart attack, premenstrual syndrome, and colon cancer, besides its ability to keep the bones healthy and to reduce the risk of osteoporosis. Other essential elements such as Fe (2.0732 mg/kg), Zn (1.0235 mg/kg), and Mn (0.2500 mg/kg) were also present but not to an appreciable amount in the extracts of T. chebula. It was concluded that due to soil nature, climatic condition, time of harvest could be a detrimental factor while reviewing the elemental profile.